Dynamic characterization of rigid foam used in finite element sports ball simulations - Burbank, S. D.; Smith, L. V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
Numerical simulation of sport ball impacts is challenging due to the varied contact conditions involved and the difficulty in characterizing nonlinear materials at high strain rates. The following considers rigid polyurethane foam used in softballs. Past works have shown that load displacement curves from viscoelastic material models do not completely agree with experiment, suggesting incorrect mechanisms of compressive deformation. Additionally, dynamic testing using a pressure bar apparatus was unable to achieve strain rates low enough, and dynamic mechanical analysis was unable to achieve strain magnitudes large enough to represent play conditions.